Distribution and stability of water-stable aggregates as affected by long-term cattle manure application to saline-sodic soil in the black soil region of northeastern China - Zhao, Ying; Meng, Qingfeng (International Journal of Agricultural and Biological Engineering, 2022)
Saline-sodic soil has a poor structure, low nutrient content, and excessive sodium in the western Heilongjiang Province, resulting in low crop productivity. Experimental treatments were established by applying manure to the soil for 5 years, 12 years, and 16 years and soil without manure application was used as a control treatment (CK). The results indicate that the application of manure significantly increased soil macroaggregates, the mean weight diameter (MWD) and the geometric mean diameter (GMD) compared to those for the CK treatment. The soil organic matter (SOM) concentration increased from 17.8 to 47.9 g/kg, the soil pH decreased from 10.18 to 7.89, and the electrical conductivity (EC) decreased from 4.92 to 0.19 dS/m. The soil exchangeable Na+ was decreased and exchangeable Ca2+ was increased in the treatments with manure application compared with the CK treatment. And a decrease in the CaCO3 content was observed in the treatment with manure. Water-stable aggregates (WSAs) of greater than 2.0 mm were the dominant factor driving the changes in the MWD, and WSAs of 1.0-2.0 mm were the dominant factor driving the changes in the GMD. The correlation matrix showed that the SOM and soil exchangeable Ca2+ concentration was positively correlated with the stability of the WSAs, while the pH, EC, and soil exchangeable Na+ were negatively and significantly correlated. We conclude that the long-term application of manure to saline-sodic soil can increase the proportion of soil macroaggregates and thus increase the stability of WSAs, as a result of the formation of soil macroaggregates mainly caused by the increase in the organic colloidal matter and soil exchangeable Ca2+, and by the decrease in soil exchangeable Na+.Keywords: cattle manure, geometric mean diameter, macroaggregate, mean weight diameter, solonetzDOI: 10.25165/j.ijabe.20221503.6800Citation: Zhao Y, Meng Q F. Distribution and stability of water-stable aggregates as affected by long-term cattle manure application to saline-sodic soil in the black soil region of northeastern China. Int J Agric & Biol Eng, 2022; 15(3): 139–145.